Design of A Laboratory Assistant Presence System Using Rfid Sensor and Web Based Esp8266 Microcontroller - Juniasyah, Deki; Sudibyo, Novi Herawadi; Muktiawan, Danang Ade (Prosiding International conference on Information Technology and Business (ICITB), 2023)
A computer laboratory is a facility that provides space and hardware (computers, printers, monitors and other equipment) as well as software for teaching, researc and development purposes in the field of information and computer technology. The computer laboratory has assistants whose job is to assist lecturers in implementing practical learning. Laboratory assistants accompany lecturers in  practical courses based on a predetermined schedule. Apart from that, there is a picket schedule that must be carried out regularly to prepare replacement assistants if an assistant is unable to attend. After completing the practical lecture, the laboratory assistant writes the summary results on a sheet of paper. This causes a lack of efficiency in monitoring picket schedules and assistance carried out by laboratory assistants. There are several innovations carried out, such as research conducted by [1] regarding the use of radio frequency identification (RFID) technology for employee attendance systems. Researchers use RFID as a sensor to perform employee attendance, nodemcu esp8266 as a microcontroller and the data obtained is displayed on the web. Based on the background of existing problems, in order to improve monitoring of laboratory assistant attendance, the author built a laboratory assistant attendance system with RFID sensors using Web-based ESP8266. From the system that has been created, monitoring of laboratory assistance and picket activities can be monitored by the laboratory coordinator via the website in real time so that it is easier and faster. Apart from that, it becomes easier for laboratory coordinators to discipline assistants who are often late for attendance. Keywords— Presence, RFID, Esp8266, Laboratory, Web